Breast cancer mortality and prediction trends in Pakistani women: alarming public health concern - Tauseef Ahmad; Mukhtiar Baig; Saba Tariq; Sundus Tariq (Journal of University Medical & Dental College, 2025)
Breast cancer is the most common cancer in Pakistani women. The incidence and mortality rates have been continuously increasing over the last three decades in the country. The number of estimated new breast cancer cases in Pakistan will increase to 66562 (R2= 0·9928) by the end of 2050. However, strengthening local collaboration between public authorities and clinical settings is a way forward for early cancer detection and proper treatment.